Hubungan Eksistensi Orang Tua di Lingkungan Sosial dengan Pola Asuh Anak Berkebutuhan Khusus - Ester Rosa Komara; Lesta Dwi Agustin; Saomy Dian Supratman; Siti Hamidah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Parents' involvement in the social environment has an important impact on the parenting of children with special needs. Parents who have a good relationship with their social environment can accelerate their child's development by providing support and assistance in developing the abilities and skills needed. The method involves a series of systematic steps through a literature study approach. The fact that children have various special needs should not be used as an excuse to avoid or neglect them. Instead, we need to raise awareness so that children can appreciate individual diversity and give attention to children with special needs. The way parents interact with their children can have an impact on their social and emotional development. Wrong parenting can lead to wrong attitudes in children and vice versa.